Is the Church Exclusive?: Comparing the Modern and Postmodern Views of the Church and the Concept of Church in 1 Peter 2:9 - Orsly W Raranta (Fakultas Filsafat Universitas Advent Indonesia, 2022)
The sift in the world culture has urged the church to revisit its understanding of its role in society. One of the important issues in the current debate in ecclesiology is about the exclusivity of the church. In his book Multicultural Kingdom,[1] Harvey Kwiyani provides the historical overview of the development of the idea of a church over the last couple of hundreds of years that leads to the concept of a multicultural church. Some scholars are trying to come up with a good balance between the relevance and the identity of the church when its authority is being challenged. Theologian such as Barry Harvey believes that the church needs to be exclusive to some degree to preserve its identity to engage inclusively with the world.[2] Scholar such as Gerard Mannion, on the other hand, believes that the idea of an exclusive church is not relevant anymore.[3] Beside looking at the socio-anthropology perspective, this study seeks to understand the concept of the church from Peter’s perspective, as is highlighted in his literary feature. It will discuss the contemporary views about the church and compare them to Peter’s ecclesiology from literary analysis.